Porphyromonas gingivalis in crevicular fluid of type 2 diabetic patients. - Britos, Maria Rosenda (2022)
Objective: To obtain the prevalence of Porphyromonas gingivalis in patients with type 2 Diabetes Mellitus. Material and method: This study was descriptive and cross-sectional. The type of sampling was for convenience and the sample consisted of 50 patients diagnosed with Type 2 Diabetes Mellitus. The degrees of Periodontitis were classified according to the criteria of Papapanou et al., (2018). The prevalence of Porphyromonas gingivalis was obtained by end-point PCR. The sample was taken in two places with greater depth of pocket. Glucose control was evaluated by measuring the percentage of glycosylated hemoglobin. The statistical analysis was performed using the InfoStat 2019 Software and the Independence Test was used using the Chi-Square statistic with 5% significance. Results: A 30% prevalence of P. gingivalis was obtained. 56% of the sample had a grade 0 of periodontitis, 24% grade I, 8% had grade II and 12% had grade III. No statistically significant difference was found between the presence of P. gingivalis and the degrees of periodontitis. Conclusions: The prevalence of P. gingivalis in the sample of patients with type 2 diabetes is 30% and its distribution is independent of the degree of periodontal disease.